Metode Shamitah (The Silent Way Method) dalam Pembelajaran Bahasa Arab - Aathifah Al Farros; Masrun (Penerbit Minhaj Pustaka, 2024)
The shamitah method (The Silent Way Method) or better known as the silent teacher method was coined in 1972 by Caleb Gategno, a linguist who applied the principles of cognitivism and philosophy in his teaching. He introduced this method through his book